Multiple-input multiple-output radar aperture optimisation - Rabideau, D.J. (IET radar, sonar & navigation, 2011)
The authors describe a process for designing low-cost, light-weight antenna apertures for use in multiple-input multiple-output (MIMO) radars. In a MIMO radar system, two or more transmitters emit independent waveforms, with the resulting reflections received by an array of receivers. Recently, MIMO radar has become a subject of great interest. In part, this interest is due to the potential for MIMO techniques to reduce radar weight and cost, while maintaining performance. However, the size of these reductions has not yet been quantified. In this article, the authors describe a process for designing optimal radar apertures. This process treats the design problem as one of minimising an objective function under performance constraints. The objective function is based upon a first-order model for the relationship between cost and performance, and is derived for systems employing active, element-digitised arrays. A systematic process for optimising the aperture's design with respect to this objective function is presented, and equations describing the optimal aperture are derived.